Future Perspectives on Biological Fabrication and Material Farming. Issue 1 (7th October 2018) - Natalio, Filipe
Abstract: What is biological fabrication? It is combining the ability of designing bioinspired molecules (chemistry) with nature's complexity and ingenious paths (biology) in order to produce new composite materials with emergent properties while being able to tailor the said materials' end‐functionality or functionalities. And what is material farming? It is the possibility to implement alternative and sustainable methodologies of biological fabrication toward larger scales, real‐life applications, and marketable products. The proof‐of‐principle is recently demonstrated for biological fabrication of fibers with tailored properties using an in vitro cotton culture and designed glucose derivatives yielding fluorescent and supermagnetic cotton fibers. This new "fabrication approach" will allow, in the future, to sustainably transform abundant raw materials into an innovative new class of composite functional materials, such as a new generation of smart textiles in the above case of cotton. This essay provides a very brief overview of the research done in cotton, the methodology used for the biological fabrication of cotton fibers with tailored properties and, finally, showcases perspectives on the future of this new and exciting research field that challenges the present fabrication methodologies that heavily rely on an old mindset toward bio‐based fabrication strategies. Abstract : Biological fabrication and material farming are emerging fields that aim to use organisms as biofactories. Understanding organism's paths and combining with their rational molecular design, it becomes possible to fabricate new composite materials with tailored end‐functionality/functionalities and improved properties that surpass traditional surface functionalization methods. This essay describes the state‐of‐the art achievements and future perspectives for this field.